The correlation matrix of Higgs rates at the LHC - Arbey, Alexandre; Fichet, Sylvain [UNESP]; Mahmoudi, Farvah; Moreau, Grégory (Springer Nature, 2016)
The imperfect knowledge of the Higgs boson decay rates and cross sections at the LHC constitutes a critical systematic uncertainty in the study of the Higgs boson properties. We show that the full covariance matrix between the Higgs rates can be determined from the most elementary sources of uncertainty by a direct application of probability theory. We evaluate the error magnitudes and full correlation matrix on the set of Higgs cross sections and branching ratios at s=7, 8, 13 and 14 TeV, which are provided in ancillary files. The impact of this correlation matrix on the global fits is illustrated with the latest 7+8 TeV Higgs dataset.
Keywords: Hadron-Hadron scattering (experiments); Higgs physics